Awra para sa ekonomiya commodification and celebrification of Wil Dasovich - Uy, Angelica Ofalsa 1995-; Vinculado, Jane O.; University of the Philippines. College of Mass Communication (2018)
"This study looks into how media performs as a major player in the commodification and celebrification of online content creators as they shift from a media platform to another. Specifically, how does the media transform beauty, travel, and lifestyle online content creators on Youtube into an object of consumption and profit? This study also inquires on how their image is transformed from online personality to a celebrity in the process as they migrate from new media to traditional media. Through textual analysis, this study analyzes how Wil Dasovich as an online content creator specific on Youtube has been manufactured to be celebrities on traditional media while also transforming them into objects of profit. To aid this analysis, Richard Dyer's Star Theory was used for the concept of celebrification. Accompanied by the theory of political economy particularly commodification, the study analyzes the said phenomenon and how their image and branding are also manufactured for consumption."
Vita.
Thesis (A.B. Broadcast Communication)--University of the Philippines Diliman
Keywords: Commodification; YouTube (Electronic resources).; Wil Dasovich (Vlogger).